2012
DOI: 10.1080/07399332.2011.562996
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and Reproductive Health Communication Between Mothers and Their Adolescent Daughters in Northern Nigeria

Abstract: We employed structured interviews and focus groups to investigate reproductive health (RH) communication practices among 184 mother-daughter pairs in Ungogo, northern Nigeria. Transcripts were analyzed using the grounded theory approach. A total of 136 mothers reported discussing RH issues with their daughters. The majority of daughters acquired RH education from their mothers. Parents were more likely to discuss marriage, menstruation, courtship, premarital sex, and sexually transmitted infections (STIs) than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 20 publications
1
34
0
Order By: Relevance
“…The low attendance of primigravida may not be unconnected with cultural practices in this setting whereby girls are expected to be 'shy' and delivered at their parents' homes under the care of their experienced mothers or grandmothers, who may not be keen on antenatal attendance. 26 Of programmatic importance is the high proportion of late booking for antenatal care seen in this study. A mere 3% of respondents registered in the first semester of their index pregnancy.…”
Section: Discussionmentioning
confidence: 97%
“…The low attendance of primigravida may not be unconnected with cultural practices in this setting whereby girls are expected to be 'shy' and delivered at their parents' homes under the care of their experienced mothers or grandmothers, who may not be keen on antenatal attendance. 26 Of programmatic importance is the high proportion of late booking for antenatal care seen in this study. A mere 3% of respondents registered in the first semester of their index pregnancy.…”
Section: Discussionmentioning
confidence: 97%
“…Men are not women's only influencers. A study that examined communication patterns between mothers and daughters in northern Nigeria found that the majority of daughters acquired reproductive health education from their mothers 36 . Yet some young women feel that they cannot talk to their mothers about their pregnancy, and are forced to rely on their friends for information, which is often inaccurate and misleading 6 .…”
Section: Who Influences Women's Health Decisions?mentioning
confidence: 99%
“…Among the published studies on parent–adolescent communication around sexuality, a wide variation exists regarding the scope, nature, and frequency of the topics discussed. Most studies use surveys, in which a list of sexual topics is presented to examine the content and extent of the communication (Schouten et al , ; Kaljee et al , ; Iliyasu et al ., ). A survey study in the Netherlands reported that choice of partner, decisions about having sex, contraceptives, unwanted sex, and body changes during puberty were talked about more than STI, premarital sex, and family values between high school students and their parents (Schouten et al , ).…”
Section: Literature Reviewmentioning
confidence: 97%
“…However, Kaljee et al () found that parents in Vietnam were more likely to talk about relationship issues with their adolescents than pregnancy and birth control. Similarly, Nigerian mothers and their daughters were more inclined to discuss marriage, menstruation, courtship, premarital sex, and STI than contraception and other reproductive issues (Iliyasu et al , ). The difference could be due to sociocultural norms in these countries, in that the Netherlands is more open about sexuality and has implemented a comprehensive system of sex education (Schouten et al , ).…”
Section: Literature Reviewmentioning
confidence: 99%